Preliminary Study: Diseminasi Produk Dokumentasi Budaya Melalui Proyek Menara Ilmu Pusat Dokumentasi Budaya - Nindya Indrasweri; Elya Riska Dwi Wahyuni; M.Salman Al Farisy (Program Studi Kearsipan, DBSMB SV UGM, 2019)
This paper aims to describe efforts to disseminate cultural documentation products that have been collected by the Cultural Documentation Center through the Menara Ilmu portal. In the archival perspective, cultural documentation products are an important component for dissemination. The management of cultural documentation products is carried out through the Total Archives approach and the neo-documentation concept. In addition, this study also provides an alternative to the optimization of the dissemination of cultural documentation products through the Culture Documentation Tower Science Project (PDB UGM UGM). The data used in this paper consists of primary data and secondary data. Primary data were collected through non-participation observations by looking at the Menara Menara Pusat cultural documentation and questionnaires with random sampling. The questionnaire was distributed to 100 respondents through Google forms. The conclusion obtained, namely the optimization of dissemination of cultural products can be implemented through